La dieta artesanal versus la dieta industrializada en pacientes con nutrición enteral domiciliaria: Una revisión integradora - Franca, Sarah Candido [UNESP]; De Paiva, Sérgio Alberto Rupp [UNESP]; Borgato, Maria Helena [UNESP]; Fontes, Cassiana Mendes Bertoncello [UNESP]; Simonetti, Janete Pessuto [UNESP]; Lima, Silvana Andrea Molina [UNESP]; Papini, Silvia Justina [UNESP] (ARAN Ediciones, 2017)
Background: Enteral nutrition therapy can be provided using comercialized products (chemically defined formulas) or blenderized home-made preparations. Objective: To perform an integrative review of the literature comparing the use of both type of formulation. Methods: In this descriptive study papers published in English, Spanish or Portuguese Brazil, in journals indexed in the databases PubMed, EMBASE, Scopus, Web of Science and Bireme without the period 2010 to 2015 were reviewed The terms “enteral nutrition, foods, formulated, diet, homemade diet industrial and artisanal diet” according to the MeSH were used for the search. Results: Twelve articles were selected. Most studies showed a level 4 of evidence and were published in journal in the higher Qualis index. Four aspects were evaluated: comparison between groups studying the clinical effects; comparison of the chemical composition of home-made products; physical-chemical and microbiological analysis of the enteral diets comes; articles on epidemiological Data on home enteral nutrition Conclusion: Industrialized diet is more suitable for patients using alternative feeding supply at home. But it has a higher cost.
Homemade diet versus diet industrialized for patients using alternative feeding tube at home - An integrative review
Keywords: Enteral nutrition; Enteral nutrition industrialized; Handmade enteral nutrition; Integrative review